Explore Publication Interests for Lecturers with Emotional Empowerment Collaboratives - Sutrisno Sutrisno (Journal Research of Social Science, Economics, and Management, 2022)
The purpose of this research is to integrate social exchange theory, social identity theory and motivation theory, so as to produce a new concept of the Emotional Empowerment Collaborative model. The next discussion describes the concept of the Emotional Empowerment Collaborative model. In social exchange among lecturers as the main asset of the university, it is necessary to form a discussion group/forum that is emotionally involved specifically to discuss issues of publication journals that are developing in a theoretical and practical competitive environment so as to provide energy/enthusiasm among group members to compete. Along with the increasing competition between universities, both at home and abroad, the quality of lecturers is high. One of the benchmarks for higher education quality is the number of scientific works produced by lecturers published in national and international journals. However, the fact is that the interest of lecturers in conducting research for publication is still low. The type of this research is exploratory research, measurement of variables by donating, collecting, professional competence and performance of lecturers' scientific publications. The results of this study are knowledge donating and knowledge collecting which are dimensions of knowledge sharing that can positively and significantly increase the publication of lecturers' scientific works in universities.